2017
DOI: 10.1016/j.biopsych.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Lesions Reduce Anxiety-like Behavior in a Human Benzodiazepine-Sensitive Approach–Avoidance Conflict Test

Abstract: BackgroundRodent approach–avoidance conflict tests are common preclinical models of human anxiety disorder. Their translational validity mainly rests on the observation that anxiolytic drugs reduce rodent anxiety-like behavior. Here, we capitalized on a recently developed approach–avoidance conflict computer game to investigate the impact of benzodiazepines and of amygdala lesions on putative human anxiety-like behavior. In successive epochs of this game, participants collect monetary tokens on a spatial grid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 71 publications
7
58
0
Order By: Relevance
“…We hypothesized that hippocampus, but not amygdala, lesions impact on the decision to approach. In our previous approach-avoidance conflict test, behavior was particularly impaired by HC lesions and anxiolytics when potential loss was high (Bach et al, 2014(Bach et al, , 2018Korn et al, 2017), such that we expected here a lesion ϫ potential loss interaction. Based on the amygdala's role in non-conflict active avoidance (LeDoux et al, 2017), we also hypothesized that amygdala but not hippocampus lesions impact on return to safety under conflict.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…We hypothesized that hippocampus, but not amygdala, lesions impact on the decision to approach. In our previous approach-avoidance conflict test, behavior was particularly impaired by HC lesions and anxiolytics when potential loss was high (Bach et al, 2014(Bach et al, , 2018Korn et al, 2017), such that we expected here a lesion ϫ potential loss interaction. Based on the amygdala's role in non-conflict active avoidance (LeDoux et al, 2017), we also hypothesized that amygdala but not hippocampus lesions impact on return to safety under conflict.…”
Section: Introductionmentioning
confidence: 71%
“…A body of literature demonstrate that the ventral (in rodents) or anterior (in humans) hippocampus (HC) is involved in behavioral control in such tests (for comprehensive reviews, see Gray and McNaughton, 2000;Ito and Lee, 2016;Kirlic et al, 2017), and somewhat less consistently, the amygdala (Kirlic et al, 2017). In humans, we have previously shown that degenerative HC (Bach et al, 2014) and amygdala lesions (Korn et al, 2017) impact on an anxiolytic-sensitive (Korn et al, 2017;Bach et al, 2018) approach-avoidance conflict test. Yet, the mechanistic function of these areas remains debated (Ito and Lee, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, while a recent study has proposed a probabilistic atlas of major nuclei based on high-resolution group data [Tyszka and Pauli, 2016], a robust method for amygdala parcellation into smaller substructures on an individual level is still missing. Finally, since we focused on white-matter connectivity, our approach was blind to direct amygdala-hippocampal connections, important for contextual conditioning [Marschner et al, 2008] or anxiety-like behaviour [Bach et al, 2014;Korn et al, 2017]. A further limitation of our study is that r Abivardi and Bach r r 3936 r the thalamus boundaries obtained from FreeSurfer did not include lateral and medial geniculate nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Although the causal contribution of the BST has yet to be explored in primates, the Ce has been shown to control defensive responses to potential threat in monkeys (Kalin, 2017;Kalin et al, 2016;Kalin, Shelton, & Davidson, 2004). Similarly, rodents, monkeys, and humans with amygdala damage exhibit a profound lack of fear and anxiety in response to a broad spectrum of learned and innate dangers (Antoniadis, Winslow, Davis, & Amaral, 2007;Bechara et al, 1995;Choi & Kim, 2010;Davis & Whalen, 2001;Feinstein, Adolphs, Damasio, & Tranel, 2011;Feinstein, Adolphs, & Tranel, 2016;Izquierdo, Suda, & Murray, 2005;Kalin et al, 2004;Korn et al, 2017;Mason, Capitanio, Machado, Mendoza, & Amaral, 2006;Oler, Fox, Shackman, & Kalin, 2016).…”
Section: Introductionmentioning
confidence: 99%